Suicidal behavior on Axis VI: Clinical data supporting a sixth axis for DSM-V - Van Orden, Kimberly A. (2011)
BACKGROUND: Oquendo and colleagues (2008; 2009) recommend that DSM-V emphasize suicide risk assessment on a sixth axis, thereby increasing regularity of suicide risk assessments. AIMS: We propose that evidence of non-redundancy with GAF is one piece of data that can serve as a starting point for a line of research establishing incremental predictive utility for a separate suicide risk assessment in the DSM framework. METHODS: A standardized suicide risk assessment protocol, as well as measures of depressive, anxious, and eating disordered symptomatology, as well as an index of comorbidity, were administered to a sample of 412 adult outpatients. RESULTS: Our data indicate that data from standardized suicide risk assessments is associated with indices of symptomatology severity as well as comorbidity, controlling for GAF. CONCLUSIONS: These results support the non-redundancy of the assessments and suggest the utility of longitudinal investigations of the predictive utility of a sixth DSM axis in the assessment of suicide risk.